PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN dan KONDISI KEUANGAN terhadap PENERIMAAN OPINI AUDIT GOING CONCERN pada PERUSAHAAN MANUFAKTUR yang terdaftar di BURSA EFEK INDONESIA - PRATIWI B51109033, PUTRI AJI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
Audit opinion of going concern is audit opinion that is produced by an auditor when a firm is indicated to have financial problem that brings about negative cash flow or failure to serve debt obligation. Determining factors of audit opinion of going concern include the size of the firm, the growth rate as well as the financial condition. The purpose of this research is to find empirical evidence of how the three factors; the size, the growth rate and the financial condition of the firm, affect the recipient of audit opinion of going concern. This research is concentrated on manufacturing firms that are listed on Bursa Efek Indonesia in the year 2009-2011, which sum up to 30 samples in total through purposive sampling method. Analysis regression logistic technic is used as the tool of data analysis. The result shows that the size, the growth rate and financial condition of the firm do not have significant effect on the recipient of audit opinion of going concern. Key word: audit opinion of going concern, size of the firm, growth rate and financial condition